2004
DOI: 10.1046/j.1529-8817.2004.03083.x
|View full text |Cite
|
Sign up to set email alerts
|

IN SEARCH OF A PHYSIOLOGICAL BASIS FOR COVARIATIONS IN LIGHT‐LIMITED AND LIGHT‐SATURATED PHOTOSYNTHESIS1

Abstract: The photosynthesis‐irradiance (PE) relationship links indices of phytoplankton biomass (e.g. chl) to rates of primary production. The PE curve can be characterized by two variables: the light‐limited slope (αb) and the light‐saturated rate (Pbmax) of photosynthesis. Variability in PE curves can be separated into two categories: that associated with changes in the light saturation index, Ek (=Pbmax/αb) and that associated with parallel changes in αband Pbmax (i.e. no change in Ek). The former group we refer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
198
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 227 publications
(215 citation statements)
references
References 103 publications
11
198
1
2
Order By: Relevance
“…Because we were not studying discrete water samples from specific depths, but rather the entire water column over a wide range of incident irradiances, light history cannot be treated in the same way as other physical factors such as temperature. As reported by Platt & Jassby (1976) and Behrenfeld et al (2004), the 2 photosynthetic parameters are correlated in many aquatic systems. Thus, temperature probably could be a good indicator of α B in large scale studies (Fig.…”
mentioning
confidence: 74%
“…Because we were not studying discrete water samples from specific depths, but rather the entire water column over a wide range of incident irradiances, light history cannot be treated in the same way as other physical factors such as temperature. As reported by Platt & Jassby (1976) and Behrenfeld et al (2004), the 2 photosynthetic parameters are correlated in many aquatic systems. Thus, temperature probably could be a good indicator of α B in large scale studies (Fig.…”
mentioning
confidence: 74%
“…Phytoplankton communities adjust their photochemical constituents and pathways towards an acclimatory state that can be characterised by their rate of cellular light absorption, saturating light-intensity and maximum rate of cellular production (Allen, 2002;MacIntyre et al, 2002;Behrenfeld et al, 2004). This dynamic process of photoacclimation is described here by s PSII,478 and s max PSII;478 , E k and ETR max RCII .…”
Section: Regulation Of Etr Max Rcii and Psii Light Absorptionmentioning
confidence: 99%
“…8, Sections 4.1 and 4.2.). As such, ETR max RCII Behrenfeld et al, 2004;Moore et al, 2006) and in turn community metabolism (Suggett, Maberly and Geider, unpubl. ) will be determined by changes in PSII light absorption.…”
Section: Regulation Of Etr Max Rcii and Psii Light Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that acclimation to a given irradiance of phytoplankton depends on the intrinsic capacity of the algae species concerned and nutrient availability (Behrenfeld et al, 2004;Falkowski and Raven, 2007). Light intensity and the efficiency of nutrient uptake were strongly coupled at lower substrate availability (Krause et al, 2012).…”
Section: Implication For Diatom Bloom Control and Diatom Surveymentioning
confidence: 98%